2021
DOI: 10.1111/sltb.12771
|View full text |Cite
|
Sign up to set email alerts
|

Financial costs to the U.S. Army for suicides by newly enlisted Soldiers

Abstract: Objective: To estimate the financial burden to the U.S. Army of suicide by enlisted Soldiers during their first year of service. Methods: This analysis included new Army enlisted Soldiers who started initial entry training from October 2012 through September 2016 and subsequently died by suicide within their first year of service. Outpatient and inpatient direct medical, direct nonmedical, recruiting, and training costs to the Army were calculated. Results: During the 48-month observational study period, 29 So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Irrespective of any normative interpretations on the appropriateness of chosen antipandemic measures, the experience reported by the Israeli and US American colleagues above [7,8] shows that strict infection control measures necessarily come with a price defined by undesired effects apart from infectious disease transmission prevention. Partly controversially discussed undesired effects among military personnel comprised overweight and diabetic diathesis due to reduced physical activity [9][10][11], age-dependent and predisposition-dependent increases in suicide rates [12][13][14], compensatory increases in risky sexual activity [15,16], affective disorders [17], higher rates of gambling problems [18] and considerable burn-out rates in military medical health staff [19]. Typical for such multifactorially influenced medical conditions, it is difficult to define which effects have been in response to the medical impact of COVID-19 itself or to side effects of the anti-pandemic response on the individuals' social life and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of any normative interpretations on the appropriateness of chosen antipandemic measures, the experience reported by the Israeli and US American colleagues above [7,8] shows that strict infection control measures necessarily come with a price defined by undesired effects apart from infectious disease transmission prevention. Partly controversially discussed undesired effects among military personnel comprised overweight and diabetic diathesis due to reduced physical activity [9][10][11], age-dependent and predisposition-dependent increases in suicide rates [12][13][14], compensatory increases in risky sexual activity [15,16], affective disorders [17], higher rates of gambling problems [18] and considerable burn-out rates in military medical health staff [19]. Typical for such multifactorially influenced medical conditions, it is difficult to define which effects have been in response to the medical impact of COVID-19 itself or to side effects of the anti-pandemic response on the individuals' social life and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has revealed that military personnel are at a higher risk than civilians of experiencing psychological disorders, including post-traumatic stress disorder (PTSD) [3][4][5][6], anxiety [7][8][9], depression [10][11][12], suicide and suicidal ideation [13][14][15], and insomnia and sleep disturbances [15][16][17]. In turn, this results in immense financial expenditure and social costs [18][19][20][21]. However, research has suggested that military personnel exhibit negative intentions to seek help and are reluctant to honestly disclose their actual psychological state because of the stigma attached to mental health problems, as well as fear of the negative impact on their professional careers [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%